Spiritual and Knowledge level, and the Acceptance of Patients with Chronic Renal Failure Who Underwent Hemodialysis - Iman Permana (Faculty of Medicine, Public Health, and Nursing, 2023)
Background: Spirituality and knowledge level has been correlated to the patient's adaptive ability to accept the condition among chronic renal failure (CRF) patients undergoing hemodialysis. Objective: To determine the relationship between the spiritual and knowledge level towards the acceptance of hemodialysis among patients in PKU Muhammadiyah Yogyakarta. Method: an analytic cross-sectional study was conducted on 101 patients who underwent hemodialysis. Data collection was done utilizing the Daily Spiritual Experience Scale (DSES) questionnaire, knowledge level of hemodialysis, and Illness Cognition Questionnaire (ICQ). The Spearman correlation test and multiple linear regression test were used to analyze the results. Results: The majority of patients have a high spiritual level, level of knowledge, and acceptance. There is a significant relationship between the spiritual level and knowledge level on the acceptance of CRF patients undergoing hemodialysis with a p-value of 0.000. Linear multiple regression analysis shows that the spiritual level has more influence on acceptance than other factors with a beta value of 0.550. Conclusion: Spiritual and knowledge levels might influence the acceptance of CRF patients undergoing hemodialysis. However, the spiritual level is the most influencing factor on acceptance. Dialysis nurses are advised to improve their ability to provide spiritual nursing care and promoting better knowledge to patients undergoing hemodialysis.